Unitatis Redintegratio: A Maiden Opening of the Ecumenical Doors of Mercy. (Hekima Review, 2016)
Prior to Vatican II Council, the reconciliatory process towards attaining Christian unity was hindered by the Church’s narcissistic statement: outside of the Church there is no salvation. This view erroneously shaped the Church’s attitude towards ecumenism thereby, preached an ecumenism of return; that is, Christian unity is explicitly realized in the mere absorption of churches into the Catholic Church. Nevertheless, the Vatican II document on ecumenism (Unitatis Redintegratio) presents a new approach to ecumenism, shying away from the language of return. Faith in the risen Christ anchored on the Trinitarian doctrine becomes henceforth the primary unifying factor of all churches into the One Church of Christ; for the self-communication of God through Christ reveals the necessity of communion. Little wonder, Pope Francis in the footstep of Unitatis Redintegratio furthered the promotion of Christian Unity through the symbolic opening of the Doors of Mercy, in that, Christians become aware that koinonia is an essential motive for God’s gift of Mercy to the world; a foundational paradigm that must lead Christians to reconciliation among themselves.